The Role of Good Governance in Affecting Technology Based Media on Sustainable Development (Case Study: Higher Education Students in University of Tehran) - Leila Nasrolahi Vosta (توسعه اجتماعی, 2023)
Several factors play a role in the process of sustainable development and are able to affect the process of development. This research aims to analyze the role of technology-based media in achieving sustainable development, emphasizing the mediating role of good governance. In this regard, the paradigm of sustainable development in Agenda 21 and the principles of good governance were used. This research is survey type in terms of strategy, applied type in terms of goal, quantitative single method in terms of data collection method, and explanatory type in terms of approach. The conceptual model of the research is based on previous studies. The population includes all postgraduate students of University of Tehran who studied in this university during the research period. In order to collect data, a survey was conducted on 450 graduate students using stratified random sampling method. Content validity and Cronbach's alpha were used to check validity and reliability. The research data was collected through a questionnaire and then analyzed using the structural equation model with the help of LISREL 8.54 software. The average indices related to the dimensions of technology-oriented media variable were 4.16, good governance variable was 3.37 and sustainable development variable was 3.61. Based on the path analysis, it was found that by increasing the use of technology-based media directly and indirectly through increasing the awareness of society members about good cooperation indicators, access to sustainable development is facilitated and accelerated. In general, it can be concluded that by using new media with the advantage of accessibility and generalization among members of the society, different societies can be put on the path of realizing sustainable development.